Protocol for the Cultural Translation and Adaptation of the World Endometriosis Research Foundation Endometriosis Phenome and Biobanking Harmonization Project Endometriosis Participant Questionnaire (EPHect) - Mis, Cise; Kofali, Gokcen; Swift, Bethan; Bahat, Pinar Yalcin; Senocak, Gamze; Taneri, Bahar; Rahmioglu, Nilufer (Frontiers Media Sa, 2021)
Endometriosis affects 10% of women worldwide and is one of the most common causes of chronic pelvic pain and infertility. However, causal mechanisms of this disease remain unknown due to its heterogeneous presentation. In order to successfully study its phenotypic variation, large sample sizes are needed. Pooling of data across sites is not always feasible given the large variation in the complexity and quality of the data collected. The World Endometriosis Research Foundation (WERF) Endometriosis Phenome and Biobanking Harmonization Project (EPHect) have developed an endometriosis participant questionnaire (EPQ) to harmonize non-surgical clinical participant characteristic data relevant to endometriosis research, allowing for large-scale collaborations in English-speaking populations. Although the WERF EPHect EPQs have been translated into different languages, no study has examined the cross-cultural translation and adaptation for content and face validity. In order to investigate this, we followed the standard guidelines for cross-cultural adaptation and translation of the minimum version of the EPQ (EPQ-M) using 40 patients who underwent laparoscopic surgery in Turkey and 40 women in Northern Cyprus, aged between 18 and 55. We assessed the consistency by using cognitive testing and found the EPHect EPQ-M to be comprehensive, informative, and feasible in these two Turkish-speaking populations. The translated and adapted questionnaire was found to be epidemiologically robust, taking around 30-60 min to complete; furthermore, participants reported a similar understanding of the questions, showing that common perspectives were explored. Results from the cognitive testing process led to minor additions to some items such as further descriptive and/or visuals in order to clarify medical terminology. This paper illustrates the first successful cross-cultural translation and adaptation of the EPHect EPQ-M and should act as a tool to allow for further studies that wish to use this questionnaire in different languages. Standardized tools like this should be adopted by researchers worldwide to facilitate collaboration and aid in the design and conduction of global studies to ultimately help those affected by endometriosis and its associated symptoms.
Keywords: endometriosis; standardization; harmonization; Turkish; questionnaire; EPHect; cross-cultural adaptation